The legal environment of business : text and cases : ethical, regulatory, global, and corporate issues - 257101 Cross, Frank B.; Miller, Roger LeRoy 373981; Cross, Frank B. 257101; Cross, Frank B. The legal environment of business : text and cases : ethical, regulatory, global, and e-commerce issues 534273 (Mason, OH : South-Western Cengage Learning, 2012)
Includes bibliographical references and index.